Exploring the Effects of Financial Technology on Economic Growth: Evidence from Indonesia - Rakhmat Prabowo; Fazar Nuriansyah; Agung Setiawan; Kinanti Geminastiti Hilmiatussadiah (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2026)
Objective: This study aims to examine the impact of fintech developments on economic growth in 34 provinces in Indonesia during the 2019-2023 period. Fintech indicators are measured through total loans disbursed, the number of borrower accounts and the number of lender accounts. This study also considers gross fixed capital formation, population, government size and HDI as human capital as control variables that affect economic growth. Method: The study applies pooled multiple linear regression to panel-structured data. To address differences in measurement scales and improve coefficient comparability, the independent variables are standardized using Z-scores prior to estimation. The analysis incorporates classical diagnostic tests including normality, multicollinearity, heteroskedasticity, and autocorrelation as well as panel-data diagnostics to assess potential cross-sectional dependence and ensure the robustness of the estimates.  Results: The findings show that the amount of loan disbursement and the number of borrower accounts affect economic growth, however, this study found that the number of lender accounts did not affect economic growth.  Novelty: This shows that the use of fintech in Indonesia is still limited to loan distribution and its potential has not been utilized optimally. This study conducted a sensitivity analysis with the results proving that the model used is robust.